Coupling Between Atrial Function and Exercise Tolerance in a Patient with Heart Failure and Atrial Fibrillation Treated with Sacubitril-Valsartan and Combined Exercise - G, Caminiti; F, Iellamo; V, D’Antoni; M, Catena; V, Morsella; M, Volterrani (Cardiology and Cardiovascular Medicine, 2021)
A 50 years old male patient with heart failure with reduced ejection fraction and permanent atrial fibrillation, referred to our centre for a cardiac rehabilitation program. He had a very limited exercise tolerance and presented a very compromised atrial function at 2D spleckle tracking echocardiography. Both exercise tolerance and left atrial function improved greatly after a comprehensive intervention including sacubitrilvalsartan administration and exercise training. These benefits, partially, persisted 8 weeks after training cessation. This is the first demonstration of an improvement in left atrial function in a patient, with heart failure and atrial fibrillation, produced by a therapeutic intervention.